2023
DOI: 10.3390/molecules28073125
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Performance Evaluation of a Temperature and Salt Resistant Hydrophobic Associative Weak Polymer Gel System

Abstract: We targeted high-temperature and highly saline old oil fields, whose environmental conditions could be attributed to the significantly high heterogeneity cause by long-term water flooding. The Huabei Oilfield was chosen as the research object. We developed a hydrophobic functional monomer–polymer with temperature and salt resistance by introducing the temperature-resistant and salt-resistant monomer NVP and a hydrophobic functional monomer into the main chain for copolymerization. We used a crosslinking agent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Xu et al [23,24] chose AM-AMPS copolymer as the gel-forming agent and studied the plugging performance of a water-soluble phenolic resin gel system under the conditions of a salt concentration of 41,110 mg/L and a temperature range of 80-90 • C. Qu et al [25] presented a gel with gelation time of 26-34 h at 55 • C using polyacrylamide, chromium acetate and water-soluble phenolic resin for the purpose of controlling water coning. In 2023, Zhi et al [26] prepared a weak gel that demonstrated excellent resistance to temperature and salt by utilizing a crosslinking agent in conjunction with the phenolic resin when the salinity was 40,300.86 mg/L at 120 • C. From the above studies, it can be found that during the preparation of gels, most of the water-soluble phenolic resins are used at temperatures between 70 • C and 90 • C, and the reservoir salinity is usually lower than 4 × 10 4 mg/L. It is because water-soluble phenolic resins would precipitate and stick to walls in high salinity water, resulting in poor stability and unsatisfactory gelling properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [23,24] chose AM-AMPS copolymer as the gel-forming agent and studied the plugging performance of a water-soluble phenolic resin gel system under the conditions of a salt concentration of 41,110 mg/L and a temperature range of 80-90 • C. Qu et al [25] presented a gel with gelation time of 26-34 h at 55 • C using polyacrylamide, chromium acetate and water-soluble phenolic resin for the purpose of controlling water coning. In 2023, Zhi et al [26] prepared a weak gel that demonstrated excellent resistance to temperature and salt by utilizing a crosslinking agent in conjunction with the phenolic resin when the salinity was 40,300.86 mg/L at 120 • C. From the above studies, it can be found that during the preparation of gels, most of the water-soluble phenolic resins are used at temperatures between 70 • C and 90 • C, and the reservoir salinity is usually lower than 4 × 10 4 mg/L. It is because water-soluble phenolic resins would precipitate and stick to walls in high salinity water, resulting in poor stability and unsatisfactory gelling properties.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al [ 25 ] presented a gel with gelation time of 26–34 h at 55 °C using polyacrylamide, chromium acetate and water-soluble phenolic resin for the purpose of controlling water coning. In 2023, Zhi et al [ 26 ] prepared a weak gel that demonstrated excellent resistance to temperature and salt by utilizing a crosslinking agent in conjunction with the phenolic resin when the salinity was 40,300.86 mg/L at 120 °C. From the above studies, it can be found that during the preparation of gels, most of the water-soluble phenolic resins are used at temperatures between 70 °C and 90 °C, and the reservoir salinity is usually lower than 4 × 10 4 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative analysis between a watersoluble phenolic resin and a phenolic composite cross-linking agent revealed that the use of water-soluble phenolic resin can lead to cost reduction and enhance the strength of the gel system. Zhi et al [20] developed a weak gel system by cross-linking a hydrophobic association polymer with a cross-linking agent based on phenolic resin. After 90 days of aging, the average viscosity retention rate of this system exceeded 80%.…”
Section: Introductionmentioning
confidence: 99%
“…After long-term water injection in oilfield development, the presence of reservoir heterogeneity and unfavorable fluid mobility ratios often leads to the formation of dominant channels in high-permeability reservoirs, resulting in inefficient or ineffective cycling in low-permeability reservoirs, thereby impacting overall field development and ultimate recovery [ 1 , 2 , 3 , 4 , 5 ]. Practice has shown that profile control technology has become an important means to improve water flooding in oilfield development, laying a solid foundation for stable production and increased oil recovery in domestic and international water-flooded reservoirs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%